2015
DOI: 10.1007/s12541-015-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and thermal conductivities of carbon fiber composites with high concentrations of carbon nanotubes

Abstract: High concentrations (1.1-3.7 wt%) of carbon nanotubes (CNTs) were incorporated into carbon fiber (CF)-reinforced epoxy composites by different fabrication methods. A mat-like form of CNT (CNT mat) was inserted between plies of CF plain-weave fabric and the composite was processed by vacuum-assisted resin transfer molding (VARTM). Two similar CNT structures, CNT mat and buckypaper, were inserted between CF woven prepreg laminates and the corresponding CF prepreg composites were fabricated by curing either in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Inclusions in polymeric matrix have been previously used to control the mechanical [Libanori et al 2012;Studart, 2013, Guttag andBoyce, 2015], thermal [Shin, Novin, and Kim, 2015], and toughness properties of the resulting composite as well as to add functionality [Arpin et al, 2010]. An essential contribution of the current work is pointing to the additional role of ead to local ben…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inclusions in polymeric matrix have been previously used to control the mechanical [Libanori et al 2012;Studart, 2013, Guttag andBoyce, 2015], thermal [Shin, Novin, and Kim, 2015], and toughness properties of the resulting composite as well as to add functionality [Arpin et al, 2010]. An essential contribution of the current work is pointing to the additional role of ead to local ben…”
Section: Discussionmentioning
confidence: 96%
“…New multifunctional materials are also composite structures. These materials optimize objectives that go beyond mechanical functions to functions such as electrical and thermal conductivities [Shin et al, 2015], optical properties [Aizenberg, et al, 2004;Arpin et al, 2010] and energy efficiency [Tarlochan and Ramesh, 2012;Arpin et al, 2010]. More recently, the area of programmable metamaterials [Engheta and Ziolkowski, 2006;Florjn et al, 2014] is emerging as a cutting edge research frontier with promising applications in several fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the second approach, CNTs may be attached to the fibre by various techniques such as chemical grafting [13,14,15], electrophoretic deposition [16,17,18], fibre sizing [19], and direct syntheses onto the fibre surface, using, for example, chemical vapour deposition (CVD) [9,20,21,22]. An improvement in electrical conductivity was found by numerous research groups [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] While carbon-based nanosheets and nanowires are known as materials with excellent mechanical and electrical properties, the sheet resistance of the coatings based on carbon is higher. Li et al 6 demonstrated that the number of graphene layers deposited on the surface had a significant effect on their conductivity and transmittance.…”
Section: Introductionmentioning
confidence: 99%